Obituary: Agnès Spycket (1921-2022) - Chevalier, Nicole (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Our colleague and friend Agnès Spycket passed away peacefully in the middle of January at her Parisian home in the rue de la Rochefoucauld. A few months earlier, she had celebrated her hundredth birthday in privacy, a privacy that she had wanted but which was especially necessary in the context of the current pandemic. With her death, after that of Pierre Amiet a few months earlier, a part of the history and memory of archaeological research in the Near East in the second half of the 20th century has disappeared.